2016
DOI: 10.12707/riv16041
|View full text |Cite
|
Sign up to set email alerts
|

Feeding a child with cerebral palsy: parents’ difficulties

Abstract: Feeding a child with cerebral palsy: parents' difficulties A Alimentação da criança com paralisia cerebral: dificuldades dos pais La alimentación de los niños con parálisis cerebral: la percepción de los padres

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 7 publications
0
17
0
2
Order By: Relevance
“…In the future, the other suggestions can be implemented. Some of challenges addressed by the caregivers are known and have been previously published in scientific literature [36,37]. Feeding problems are prevalent in children with CP (21-58%) and some of them were discussed during the meetings [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, the other suggestions can be implemented. Some of challenges addressed by the caregivers are known and have been previously published in scientific literature [36,37]. Feeding problems are prevalent in children with CP (21-58%) and some of them were discussed during the meetings [36].…”
Section: Discussionmentioning
confidence: 99%
“…Some of challenges addressed by the caregivers are known and have been previously published in scientific literature [ 36 , 37 ]. Feeding problems are prevalent in children with CP (21–58%) and some of them were discussed during the meetings [ 36 ]. Nevertheless, the main problems expressed by caregivers were related to very practical issues, such as meal preparations and how to adapt its textures, how to prepare nutritious food, and other issues.…”
Section: Discussionmentioning
confidence: 99%
“…Un producto no atractivo puede ser percibido como ineficiente e ineficaz (Mugge & Schoormans, 2012). Además, los resultados destacan que los elementos relacionados con la percepción estética de un producto de apoyo, puede contribuir con el estigma social, como ya han señalado Shinohara & Wobbrock, 2011, Marques & Sá, 2016, y Vasquez et al, 2016. De hecho, las personas que no son usuarias de productos de apoyo emiten juicios desde el punto de vista de su percepción estética, aumentando el estigma que envuelve la interacción entre usuario-actividad-producto.…”
Section: Discusionesunclassified
“…National and international studies have shown that children and adolescents with CP have an increased risk of malnutrition. 7 , 8 , 9 , 10 , 11 Thus, it is essential to identify risk factors for this clinical condition early in order to improve the prognosis of these individuals. Epidemiological investigations have presented different behaviors for the nutritional therapy of individuals with CP, ranging from recommending the use of nutritional supplements to the best route for administering the diet.…”
Section: Introductionmentioning
confidence: 99%